A direct method for measuring surface area of polymer mesh using synchrotron x-radiation microComputed tomography: a pilot study. (25th September 2019) - Jordan, Sumanas W; Janes, Lindsay E; Sood, Rachita; Jakus, Adam E; Soriano, Carmen; Stock, Stuart R; Dumanian, Gregory A
Abstract: Mesh products are critical for successful long term surgical repair of many anatomic defects, including hernias and pelvic prolapse. Biocompatibility of polymeric mesh depends on the foreign body response- how the tissues react to physicochemical properties, including porosity and mesh 'weight'. We postulate that effective surface area, the total filament area in contact with the tissues, is an important variable for long-term repair strength. We present a technique utilizing synchrotron x-radiation microComputed Tomography (microCT) to calculate the effective surface area of polymeric meshes. Six representative polypropylene-based hernia meshes, including composite meshes, were studied: Ethicon PROLENE TM, Ethicon PROLENE TM Soft Mesh, Ethicon PHYSIO MESH TM, Ethicon ULTRAPRO TM, Atrium PROLITE TM Mesh, and Bard ® Soft Mesh. Ethicon PROLENE TM, a heavy weight mesh, had the highest effective surface area at 6.44 cm 2 cm −2 and Ethicon ULTRAPRO TM, a composite light-weight mesh, had the lowest effective surface area at 0.62 cm 2 cm −2 . We conclude that this technique can reliably be used to further classify mesh, as manufacturers and surgeons continue to optimize the safety profile of these implants.